Determinant of Adult Education Program: A Critical Analysis of Adult Education in Some Selected Training Centers of Eastern Regions - Seyoum, Yilfashewa; Amdemeskel, Yonas (Bina Nusantara University, 2016)
The purpose of this study was to analyze the factors affecting adult education in the eastern part of Ethiopia. The study employed a survey design that involved qualitative and quantitative approaches. A stratified random sampling technique was used to select 515 male and 285 female respondents. A questionnaire and an interview for collecting information from the primary sources were designed and implemented. Data were analyzed with linear correlation and Ordinary Least Square (OLS) regression. The findings indicated that the relationship of overall adult learning achievement to assessment of learning (r = 0,29, P < 0,01), and the methods used by facilitators (r = 0,23, P < 0,01) is positive and significant. The regression model demonstrated that overall adult learning condition is significantly affected by variables such as relevance of the content, methods of teaching, assessment of learning outcome, and locality of the adult education learners.